2021
DOI: 10.1099/mgen.0.000573
|View full text |Cite
|
Sign up to set email alerts
|

Genomic epidemiology of tuberculosis in eastern Malaysia: insights for strengthening public health responses

Abstract: Tuberculosis is a leading public health priority in eastern Malaysia. Knowledge of the genomic epidemiology of tuberculosis can help tailor public health interventions. Our aims were to determine tuberculosis genomic epidemiology and characterize resistance mutations in the ethnically diverse city of Kota Kinabalu, Sabah, located at the nexus of Malaysia, Indonesia, Philippines and Brunei. We used an archive of prospectively collected Mycobacterium tuberculosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Interestingly, a sublineage in the Napier's scheme 6 not present in our main dataset was L1.2.1, with most isolates being from patients in Europe. Therefore, we inferred a separate phylogeny of L1.2 isolates that included 410 isolates from our dataset and additional 364 isolates from Napier et al 6 and other recent studies 10 , 14 (Fig. 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a sublineage in the Napier's scheme 6 not present in our main dataset was L1.2.1, with most isolates being from patients in Europe. Therefore, we inferred a separate phylogeny of L1.2 isolates that included 410 isolates from our dataset and additional 364 isolates from Napier et al 6 and other recent studies 10 , 14 (Fig. 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Supplementary Table S3 shows the distribution of samples across countries and sublineages. We also obtained additional 364 L1.2 isolates from three recent studies 6 , 10 , 14 . This set was analyzed together with the 410 L1.2 isolates from the main dataset, referred to as the L1.2 dataset ( n = 364 + 410 = 774) (Supplementary Table S2 ).…”
Section: Methodsmentioning
confidence: 99%
“…It can be argued that the small window screening period used in this intervention (3months), might be too short to find recent contacts or older primary cases (35). Molecular epidemiology studies should shed more light on the nature of the link between IC and TB cases found among contacts (36)(37) (38).…”
Section: Discussionmentioning
confidence: 99%
“…It can be argued that the small window screening period used in this intervention (3months), might be too short to find recent contacts or older primary cases(35). Molecular epidemiology studies should shed more light on the nature of the link between IC and TB cases found among contacts (36)(37)(38). Other important questions such as what the best window period for screening is, whether there is a need for time-separated screening visits, the role of HIV status in TB transmission and what role gender plays on the impact of ACF activities need to be answered to refine ACF intervention designs.…”
Section: Discussionmentioning
confidence: 99%
“…Another population-based, retrospective TB study in Shanghai, China (referred to as CTB), utilized both VNTR and WGS strategies to detect the recent transmission of 324 multidrug-resistant (MDR) tuberculosis strains and demonstrated WGS can measure the heterogeneity of drug-resistant mutations within and between hosts and help to determine the transmission patterns of MDR TB ( Yang et al , 2017 ). Along with the UKTB and CTB studies, multiple studies from around the world have pointed out that the resolution of WGS is superior to that of MIRU-VNTR typing and that epidemiological links can be traced more accurately ( Bainomugisa et al , 2021 ; Bjorn-Mortensen et al , 2016 ; Folkvardsen et al , 2017 ; Ford et al , 2012 ; Jiang et al , 2020 ).…”
Section: Introductionmentioning
confidence: 99%